MOTIVATIONAL DYNAMICS IN STUDENT EXECUTIVE ORGANIZATIONS: EVIDENCE FROM A VOCATIONAL SCHOOL CONTEXT - Firly Aulia Zahra; Ghina Ambarwulan; Ranita Rosaria; Maulana Amirul Adha (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
Student executive organizations play an important role in developing students’ leadership and professional competencies, yet maintaining motivation within these organizations remains a challenge. This study aims to investigate the motivational dynamics of students in a student executive organization within a vocational school context. This research employs a qualitative descriptive approach with purposive sampling, data were collected through interview and observation, and analyzed using the Miles and Huberman interactive model. The findings indicate that self-consistency is the primary intrinsic motivator sustaining students’ engagement, while social support from family and peers serves as a significant external source of motivation; furthermore, motivational stability is maintained through a positive mindset and effective time management. These findings highlight that motivation is shaped by the interaction of internal commitment, social environment, and self-regulation strategies. This study contributes by providing contextual insights into motivational dynamics in vocational student organizations and offering practical implications for enhancing student engagement and organizational performance.